Adjusting to robots: worker-level evidence - Dauth, Wolfgang; Findeisen, Sebastian; Suedekum, Jens; Woessner, Nicole (Minneapolis, 2018)
"We estimate the effect of industrial robots on employment, wages, and the composition of jobs in German labor markets between 1994 and 2014. We find that the adoption of industrial robots had no effect on total employment in local labor markets specializing in industries with high robot usage. Robot adoption led to job losses in manufacturing that were offset by gains in the business service sector. We analyze the impact on individual workers and find that robot adoption has not increased the risk of displacement for incumbent manufacturing workers. They stay with their original employer, and many workers adjust by switching occupations at their original workplace. The loss of manufacturing jobs is solely driven by fewer new jobs for young labor market entrants. Moreover, we find that, in regions with higher exposure to automation, labor productivity increases while the labor share in total income declines."